KUAT TEKAN BETON YANG TERJADI AKIBAT PENGGUNAAN PECAHAN GENTENG DARMASABA SEBAGAI PENGGANTI SEBAGIAN AGREGAT KASAR - I Made Sastra Wibawa; I Gede Angga Diputera; I Ketut Diartama Kubon Tubuh (Program Studi Teknik Sipil Fakultas Teknik Universitas Mahasaraswati Denpasar, 2021)
The need for concrete as a construction material to support infrastructure development is still very large, this is because concrete is still believed to be a reliable material for building construction. The availability of concrete mixtures in nature is running low because it continues to be taken for development. Realizing this, it is necessary to innovate in the future to find materials as a substitute for sand and coral, which are decreasing in number. This research tried to use the tile fragments of Banjar Tegal, Darmasaba, as a substitute for some of the coarse aggregate needed in the concrete mixture. The purpose of this study was to determine whether the Banjar Tegal tile fragments qualify as a concrete mixture according to the grading requirements, and how much compressive strength occurs. Tile fraction samples were taken in Banjar Tegal, Darmasaba, Abiansemal, Badung, while the research was carried out at the Concrete Laboratory, Faculty of Engineering, Unmas Denpasar. Tests were carried out using cylindrical specimens of size 15 x 30 cm, the mixture was made in five treatments with 8 pieces of each treatment, and testing was carried out on 28 days old concrete. The results show that the Banjar Tegal tile fragments can meet the requirements of aggregate gradation as a concrete mixture, and according to the laboratory test results the compressive strength of the concrete still meets the requirements in accordance with the concrete plan, but a slight decrease is proportional to the percentage of replacement made. The complete results are P0 = 237.74 Kg / Cm²; P1 = 234.63 Kg / Cm²; P2 = 232.05 Kg / Cm².; P3 = 229.22 Kg / Cm²; P4 = 225.27 Kg / Cm². Thus, the tile fragments of Banjar Tegal, Darmasaba can be used as a substitute for some of the coarse aggregate in the concrete mixture.